Traffic Management Analysis on the Bunggasi Road Section of Kendari City - Makmur, Muzammil; Makmur, Muammar (Riviera Publishing, 2025)
City which is located in the Andounohu area. Based on the spatial map of the CBD area of Kendari City where the dominant activity that occurs on the road is economic activities which are marked by rows of Shop Houses (Shophouses), Markets, Mosques, Banks, Restaurants and so on. One of the factors that causes changes and increases in the shape of the area on this road is the existence of Marina Mart shopping centers and Anduonohu Market. The research